2008
DOI: 10.1007/s00405-008-0816-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after tympanoplasty with and without mastoidectomy for perforated chronic otitis media

Abstract: The objectives of the retrospective study, performed at a tertiary referral center, were to examine the prognostic factors predicting long-term outcomes of tympanoplasty for perforated chronic otitis media (COM) and to determine whether mastoidectomy can be avoided during tympanoplasty for perforated COM. Between 1987 and 2002, 213 patients with perforated COM underwent tympanoplasty by the same surgeon and were followed for more than 5 years. Postoperative hearing outcomes were considered successful, if the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 6 publications
3
54
1
Order By: Relevance
“…[22] Tos recommended mastoidectomy for discharging ears, and Mishiro et al reported that they do not routinely perform mastoidectomy for simple tympanic membrane perforations accompanied by chronic otitis media. [23] In the present study, the rate of graft success after tympanoplasty was significantly higher in patients with epitympanic patency (p<0.001). In addition, the presence of …”
Section: Ent Updatessupporting
confidence: 44%
“…[22] Tos recommended mastoidectomy for discharging ears, and Mishiro et al reported that they do not routinely perform mastoidectomy for simple tympanic membrane perforations accompanied by chronic otitis media. [23] In the present study, the rate of graft success after tympanoplasty was significantly higher in patients with epitympanic patency (p<0.001). In addition, the presence of …”
Section: Ent Updatessupporting
confidence: 44%
“…Both the canal wall up and the canal wall down technique can be applied with acceptable audiometric results [6]. Although the mastoid and tympanic antrum seem to be filled with lesions as shown by high-resolution computerized tomography (HRCT) and magnetic resonance (MR) imaging, the available literature supports the notion that therapeutic mastoidectomy does not have any additional benefits for the management of noncholesteatomatous COM [3,[7][8][9][10]. However, we are not sure if it has the same long-term outcomes without performing mastoidectomy for noncholesteatomatous COM in variable preoperative infections.…”
Section: Introductionmentioning
confidence: 75%
“…Mastoidectomy does not produce any additional benefits for the patients. Mishiro et al [10] performed tympanoplasty in 213 patients with tympanic membrane perforations caused by chronic suppurative otitis media and followed them for more than 5 years. Logistic regression analysis showed that the ossicular chain was the only factor for evaluating long-term hearing outcomes after surgery, and even in active infection conditions, mastoidectomy was unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that tympanoplasty without mastoidectomy could be performed under local anesthesia which might be preferred especially in the elderly and patients with medical complications. [15] In this study also the risks caused by mastoidectomy were reported. As far as we know, sensorineural hearing loss may occur because of drill trauma, secondary meningitis may develop because of dura mater trauma at tegmen tympani zone, massive bleeding may be served due to sigmoid sinus trauma and facial nerve injury may occur during mastoidectomy.…”
Section: Discussionmentioning
confidence: 71%